Analisis Faktor yang Mempengaruhi Keterlambatan Penyelesaian Studi Mahasiswa Pendidikan Tata Rias Universitas Negeri Jakarta - Awalia, Fadilla Putri; Ayuningtyas, Nurina; Ambarwati, Neneng Siti Silfi (YASIN, 2024)
The purpose of this research is to find out what factors affect the delay in completing studies for students in the Cosmetology Education study program, State University of Jakarta. The research method that to be used is a survey research method through a quantitative approach. The population in this study were all cosmetology education students from the 2017, 2018 and 2019 classes at Jakarta State University who were still active in semester 119. From the data obtained, there were approximately 67 students. Data Analysis Techniques In quantitative research with descriptive statistics. The factors that influence students' late completion of studies are internal factors, namely: category percentage, motivation and interest which can be categorized as the "Enough" interval. Meanwhile, external factors: the percentage of categories of academic problems and personal social problems can be interpreted at “high intervals”. This means that external factors have a high influence on delays in completing student studies.